The Model of Integral Islamic Boarding School Education and Its Implications on Student Character (Case Study at Islamic Boarding School MTS N 1 Tegal) - Ramadhoni, Muhammad Abdul; Amin, Muhammad Ikhsanul; Yani, Ahmad (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to analyze the integral education model at the Islamic Boarding School (IBS) MTsN 1 Tegal and its implications for the formation of student character. Integral education at IBS MTsN 1 Tegal combines the national curriculum with Islamic religious values, and integrates classroom learning activities with daily life in the dormitory. Through a qualitative method with a case study approach, this study collected data from interviews, observations, and document analysis. The results of the study indicate that integral education at IBS MTsN 1 Tegal is effective in forming the character of students who are religious, independent, disciplined, and have good morals. The implementation of this education includes the habituation of Islamic values, strengthening morals, extracurricular activities based on Islam, and social interactions that support the development of empathy and social responsibility. This model faces challenges such as limited facilities and the influence of global culture, but also has great opportunities through community support for Islamic-based education and innovation in educational technology. In conclusion, the integral education model at IBS MTsN 1 Tegal makes a significant contribution to the formation of a generation with Islamic character and is ready to face the challenges of the modern era.